Kontestasi Hadis di Era Multimedia: Kajian Hadis di Youtube Mengenai Alat Musik - Hafidhuddin, Hafidhuddin (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2022)
This research raises YouTube as the most popular media by the people in Indonesia. In the era of technology and communication, hadith as a study can not only be witnessed in offline public spaces, but also online. As was the case regarding the hadiths regarding musical instruments that were contested via YouTube, between UAH and Gus Baha. This development has brought changes to the study of hadith, based on the explanation given by UAH and Gus Baha, there are positive and negative perceptions felt by the Indonesian people, based on a review of the comments contained in the YouTube channel in question. Actually, this kind of issue has been discussed by previous scholars. Various media exist, it is not uncommon for religious studies to be spread along with their respective interests. This situation also affects the development of other religious issues, including the study of hadith.